A pilot study to assess the effect of acute exercise on brain glutathione. (2nd January 2018) - Rai, Sahara; Chowdhury, Alimul; Reniers, Renate L. E. P.; Wood, Stephen J.; Lucas, Samuel J. E.; Aldred, Sarah
Abstract: The brain is highly susceptible to oxidative stress due to its high metabolic demand. Increased oxidative stress and depletion of glutathione (GSH) are observed with aging and many neurological diseases. Exercise training has the potential to reduce oxidative stress in the brain. In this study, nine healthy sedentary males (aged 25 ± 4 years) undertook a bout of continuous moderate intensity exercise and a high-intensity interval (HII) exercise bout on separate days. GSH concentration in the anterior cingulate was assessed by magnetic resonance spectroscopy (MRS) in four participants, before and after exercise. This was a pilot study to evaluate the ability of the MRS method to detect exercise-induced changes in brain GSH in humans for the first time. MRS is a non-invasive method based on nuclear magnetic resonance, which enables the quantification of metabolites, such as GSH, in the human brain in vivo . To add context to brain GSH data, other markers of oxidative stress were also assessed in the periphery (in blood) at three time points [pre-, immediately post-, and post (∼1 hour)-exercise]. Moderate exercise caused a significant decrease in brain GSH from 2.12 ± 0.64 mM/kg to 1.26 ± 0.36 mM/kg ( p = .04). Blood GSH levels increased immediately post-HII exercise, 580 ± 101 µM to 692 ± 102 µM ( n = 9, p = .006). The findings from this study show that brain GSH is altered in response to acute moderate exercise, suggesting that exercise may stimulate an adaptive response in the brain. Due to the challenges in MRS methodology, this pilot study should be followed up with a larger exercise intervention trial.